Electrochemical Biosensors Designed with Coordination Compounds: Recent Advancements and Future Perspectives - Abhay Nanda Srivastva; Kriti Milan; Netra Pal Singh; Dharm Veer Singh; Manish Kumar; Vishal Chaudhary; Samiksha Dabas (ECS Sensors Plus)
Electrochemical (EC) biosensors based on coordination compounds have risen as an impeccable way to detect biological moieties due to their cogent results. Metal complexes are widely recognized as they have been employed in many areas of human wellness. Starting with detection of oxygen, glucose, and urea to now detecting pathogens like SARS-CoV-2, EC-sensors are gaining attention across many fields. In the medical field, they hold an important place as they can diagnose harmful elements/diseases in early stages, lowering the risk of death. Thus, the innovative research is essential to control impairments of microbial actions by advancing metal complex based EC-biosensors.